2019
DOI: 10.1590/1678-4324-2019180731
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cytotoxic Evaluation of Silver and Gold Nanoparticles Produced with Aqueous Extract of Lavandula dentata L. in Relation to K-562 Cell Line

Abstract: Metallic nanoparticles have great potential as a chemotherapeutic agent. The aim of this study was to develop and characterize silver and gold nanoparticles using a simple method, as well as evaluating the potential cytotoxic activity in relation to the K-562 cell line. For the synthesis, a solution containing the metallic ions was subjected to magnetic stirring with the aqueous extract of Lavandula dentata L. and a change of colour was observed. With the data obtained from the analyses we concluded that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Is an expected result, sice hydrothermal synthesis, the method employed for AgNPs production in this work, allows controlling particles morphology and size during the synthesis [14]. Justus and coauthors [24] obtained silver nanoparticles from natural sources and observed its size around 30nm, results close to those found in this work.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Is an expected result, sice hydrothermal synthesis, the method employed for AgNPs production in this work, allows controlling particles morphology and size during the synthesis [14]. Justus and coauthors [24] obtained silver nanoparticles from natural sources and observed its size around 30nm, results close to those found in this work.…”
Section: Discussionsupporting
confidence: 81%
“…SEM is an important technique used for the study of nanoparticle morphology and size, as well as allowing for the analysis of sample homogeneity [24] and, according to its images, most particles covering orthodontic wires presented spherical-like shape and nanometric size, inferior to 20nm. Is an expected result, sice hydrothermal synthesis, the method employed for AgNPs production in this work, allows controlling particles morphology and size during the synthesis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Justus et al compared the anti-leukemic activity of the AuNPs and AgNPs, which were fabricated using the aqueous extract of Lavandula dentata L, against K-562 cells using MTT assay. After 72 h of treatment, 250 µL of AuNPs stock (0.1 mM) induced 76.2% cell inhibition, whereas AgNPs induced 36.1% reduction in cell viability [115] .…”
Section: Green-synthesized Metallic Nanoparticles For the Treatment O...mentioning
confidence: 99%
“…However, these results from the research presented may be useful to support the use of lavender-distilled essential oils as a promising anticancer agent in cancer treatment, as well as in vivo studies to identify mechanisms underlying anti-cancer effects [ 30 ]. Another study has shown that nanoparticles (LdAuNPs) produced with lavender have great potential to reduce K-562 cell viability, a myelogenous leukemia cell line [ 45 ].…”
Section: Main Textmentioning
confidence: 99%